2016
DOI: 10.1007/s11356-016-7292-y
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of precious and pollutant metals in biomass of cultured water hyacinth (Eichhornia crassipes)

Abstract: The aim of this study was to investigate the overall root/shoot allocation of metal contaminants, the amount of metal removal by absorption and adsorption within or on the external root surfaces, the dose-response of water hyacinth metal uptake, and phytotoxicity. This was examined in a single-metal tub trial, using arsenic (As), gold (Au), copper (Cu), iron (Fe), mercury (Hg), manganese (Mn), uranium (U), and zinc (Zn). Iron and Mn were also used in low-, medium-, and high-concentration treatments to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
0
24
0
1
Order By: Relevance
“…Newete et al . (2016), showed that manganese accumulation increased with greater concentrations in the growth medium 31 . The initial concentrations did not vary enough within this study to fully assess this assertion.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Newete et al . (2016), showed that manganese accumulation increased with greater concentrations in the growth medium 31 . The initial concentrations did not vary enough within this study to fully assess this assertion.…”
Section: Resultsmentioning
confidence: 96%
“…(2015) and Newete et al . (2016) most previous work has examined removal under nutrient starving conditions, whereas in this study, there are many other nutrients present and available within the river water, as would be the case in a “real” remediation setting within any river 21 , 31 , 38 .…”
Section: Resultsmentioning
confidence: 99%
“…This is with the aim of protecting the plants against the harmful effects of high levels in leaves, where the photosynthetic processes take place [58,59]. Aquatic plants capable of accumulating up to 5000 mg of metals per kilogram of dry plant biomass or those with BCF > 1000 are considered as hyper-accumulators of PTMs [28,57]. In the present work, the total amount of metals accumulated by Water hyacinth plants was below 5000 mg/kg d.w.…”
Section: Potential Toxic Metal In Water Hyacinth Plantsmentioning
confidence: 56%
“…Water hyacinths samples were washed three times with Milli-Q deionized water without a subsequent washed with deionized acidified water. According to Newete [28], the acid wash eliminates the portion of the adsorbed contaminants such as PTMs. Therefore, by omitting the acid wash, the adsorbed and absorbed portions of the contaminants remain in the plants for further analysis.…”
Section: Collection Of Water Hyacinth Plants Samplesmentioning
confidence: 99%
See 1 more Smart Citation